2007
DOI: 10.1021/ol070492l
|View full text |Cite
|
Sign up to set email alerts
|

Diastereomeric Recognition of Chiral Foldamer Receptors for Chiral Glucoses

Abstract: [reaction: see text] Three chiral aromatic hydrazide foldamers have been designed and synthesized, in which two R- or S-proline units were incorporated at the terminals of their backbones. The 1H NMR, circular dichroism (CD), and fluorescent experiments and molecular dynamics simulations revealed that the foldamers adopted a chiral helical conformation and complexed alkylated glucoses in chloroform with a good diastereomeric selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 23 publications
1
59
0
Order By: Relevance
“…Moreover, carbohydrate recognition in organic media can be biomimetic in the sense of mimicking recognition at the membrane-cytosol interface, especially if extraction from water can be demonstrated. Accordingly, there has been considerable work in this area over the past 20 years, as recorded in a number of reviews [24,36,48,49] and recent articles [50][51][52][53][54][55][56][57][58][59]. For reasons of space, we will not attempt a further discussion of this work but will proceed to our major topic of carbohydrate recognition in water.…”
Section: Synthetic Lectin Design Principlesmentioning
confidence: 99%
“…Moreover, carbohydrate recognition in organic media can be biomimetic in the sense of mimicking recognition at the membrane-cytosol interface, especially if extraction from water can be demonstrated. Accordingly, there has been considerable work in this area over the past 20 years, as recorded in a number of reviews [24,36,48,49] and recent articles [50][51][52][53][54][55][56][57][58][59]. For reasons of space, we will not attempt a further discussion of this work but will proceed to our major topic of carbohydrate recognition in water.…”
Section: Synthetic Lectin Design Principlesmentioning
confidence: 99%
“…However, studies on the recognition behavior of linear receptors were reported in 1970s, while Vögtle et al reported the complexing properties of oligo(ethylene glycol) derivatives toward metal ions [6] . More recently, the present authors and Huc et al found that rationally designed hydrogen bonded aromatic amide or hydrazide-based foldamers could bind neutral or ionic guests in more selective manner [7][8][9][10][11][12][13][14][15] , which mainly depends on the size of their cavity, through multiple intermolecular hydrogen bonds. For all the reported oligomers, the presence of a successive network of intramolecular hydrogen bonds forces the backbones to adopt well-predicted folded or helical conformations, which significantly reduces the binding-initiated negative entropy.…”
Section: Introductionmentioning
confidence: 64%
“…We previously reported a class of aromatic hydrazidebased foldamers forced by successive intramolecular hydrogen bonds to form helical conformation [7,11,12] , in which half of the C== O groups are located inward and thus efficiently bind alkylated saccharides via multiple intermolecular hydrogen bonds in chloroform. It was envisioned that the decrease of the intramolecular hydrogen bonds would increase the conformational flexibility, which might lead to the reduction of the binding capacity.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…When two chiral proline groups were appended to the ends of the backbone, the resulting foldamers 17a-c produced helicity bias, which was evidenced by circular dichroism experiments. [35] In order to investigate the stacking of this class of folded backbones, foldamers 18a and 18b were also prepared. [36] The introduction of the amphiphilic amide side chains provided the oligomers with solubility in polar organic solvents, in which the folded backbone stacked strongly to generate vesicles or organogels, depending on the solvents used.…”
Section: Aromatic Urea and Hydrazide Backbonesmentioning
confidence: 99%